The Influence of Product Quality and Promotion on Purchasing Decisions of Janji Jiwa Palembang Coffee - Agusty, Reza Madira; Widagdo, Herry (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the Influence of Product Quality and Promotion on the Purchase Decision of Janji Jiwa Palembang Coffee. This study uses a descriptive quantitative method and with a sample of 399 respondents. The data analysis method used non-probability sampling, purposive sampling, and multiple regression with the SPSS version 21 test tool. Based on the results of the study, it was shown that the variables of Product Quality, Motivation, Promotion, and Lifestyle had a significant and positive effect partially or simultaneously on the Purchase Decision of Janji Jiwa Coffee Palembang.